Simulation of direct current microgrid and study of power and battery charge/discharge management [Simulación de microred en corriente continua y estudio de gestión de potencia y de carga/descarga de baterías] - Mírez J. (2017)
J. L. Mírez thanks to the National Council of Science and Technology of Peru (CONCYTEC) for funding his doctoral research at National University of Engineering and partially supported by MIGEDIR project: Microgrids with Renewable Distributed Generation (code 713RT046) from the Science and Technology for Development Iberoamerican Program (CYTED), also at Development of Renewable Energy Sources (CEDER) of CIEMAT in Soria, Spain; Electric Power System Research Group of Sandia National Laboratories in Albuquerque, New Mexico, USA; and, Center for Information and Communication Technologies (CTIC) of the National University of Engineering, Lima, Peru.